The distribution of Willowherb Hawkmoth Proserpinus proserpina (Pallas, 1772) (Lepidoptera, Sphingidae) in Croatia - Koren, Toni (Acta entomologica slovenica (Ljubljana), 2019)
The Willowherb Hawkmoth (Proserpinus proserpina) is a rare and local moth species bound to thermophilous forest edges and wetland habitats. It is listed in the Annex IV of the Habitats Directive. So far, only several historical records existed for this species in Croatia, the last ones being more than 30 years old. Here an overview is presented of the known historical records, as well as five new records of P. proserpina from different regions of the country. The known distribution has been significantly expanded toward the south. The species has been confirmed in the Dalmatian mainland in Neretva river delta and for the first time recorded on two Adriatic islands, Murter and Dugi Otok. In order to asses its conservation status, a monitoring plan should be developed and implemented in Croatia.
Keywords: butterflies; Croatia; Hrvaška; Insecta; Lepidoptera; metulji; new records; nove najdbe; Proserpinus proserpina; Žuželke